f) + (+13) + (-5) + (-1). (-2)
Soluções para a tarefa
Respondido por
0
Resposta:
Primeiro temos que fazer as operações de multiplicação depois a de soma
f) 13 -5 +2 = 8 + 2 = 10
Espero ter ajudado!
Respondido por
0
Explicação passo-a-passo:
f(x)= 2x-5
f(13)=2•(13)-5=26-5=21
f(1/2)=2•(1/2)-5=2/2-5=1-5=-4
f(5)= 2•(5)-5=10-5=5
Perguntas interessantes
Ed. Física,
8 meses atrás
Português,
8 meses atrás
História,
8 meses atrás
Biologia,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás